The Effects of Criminal Embeddedness on School Violence in Brazil - Silva, Braulio Figueiredo Alves da; Higgins, Silvio Segundo Salej; Oliveira, Elenice DeSouza (International Journal of Criminology and Sociology, 2019)
This study examines the influence of criminal embeddedness on the intensity of criminal behavior among primary and secondary school students in a large Brazilian city. A database conceived by the Center for the Study of Crime and Public Security at the Federal University in Minas Gerais is used to analyze the involvement of youths displaying delinquent behavior at home or at school and how school performance and peer relationships are effected. Based on differential association and learning theories, the main hypotheses are (1) the greater the criminal embeddedness, the lower the degree of school satisfaction as well as future expectation of continued higher education, and (2) the greater the criminal embeddedness, the greater the risk of the intensity of deviant and criminal behavior. Applying statistical linear and nonlinear regression models, findings indicate that the criminal embeddedness has a negative and statistically significant association with the student’s level of school satisfaction.